Safety and efficacy of pharmacological thromboprophylaxis for hospitalized patients with cirrhosis: a single‐center retrospective cohort study. (15th June 2015) - Shatzel, J.; Dulai, P. S.; Harbin, D.; Cheung, H.; Reid, T. N.; Kim, J.; James, S. L.; Khine, H.; Batman, S.; Whyman, J.; Dickson, R. C.; Ornstein, D. L.
Summary Background Hospitalized patients with cirrhosis are at increased risk for venous thromboembolism (VTE). The benefits and risks of pharmacological thromboprohylaxis in these patients have not been well studied. Objectives To examine the safety and efficacy of pharmacological VTE prophylaxis in hospitalized cirrhotic patients. Patients/Methods Retrospective cohort study of patients with cirrhosis hospitalized at an academic tertiary care referral center over a 5‐year period. Results Six hundred hospital admissions accounting for 402 patients were included. VTE prophylaxis was administered during 296 (49%) admissions. Patients receiving VTE prophylaxis were older (59 years vs. 55 years, P < 0.001), had longer lengths of stay (9.6 days vs. 6.8 days, P = 0.002), and lower Model for End‐Stage Liver Disease scores (13.2 vs. 16.1, P < 0.001). In‐hospital bleeding events (8.1% vs. 5.5%, P = 0.258), gastrointestinal bleeding events (3.0% vs. 3.2% P = 0.52), new VTE events (2.37% vs. 1.65%, P = 0.537), and mortality (8.4% vs. 7.3%, P = 0.599) were similar in the two groups. VTE prophylaxis did not reduce the risk of VTE (odds ratio 0.94, 95% confidence interval 0.23–3.71), and patients receiving unfractionated heparin, but not low molecular weight heparin, were at increased risk for in‐hospital bleeding events (odds ratio 2.38, 95% confidence interval 1.15–4.94 vs. 0.87, 0.37–2.05, respectively). Conclusion The rate of VTE in this cohort of hospitalized cirrhotic patients was low and was unaffected by pharmacological thromboprophylaxis. Unfractionated heparin was associated with an increased risk for in‐hospital bleeding, suggesting that if thromboprophylaxis is indicated, low molecular weight heparin may be favored.